Risk of premature luteinization in IVF cycles and its impact on clinical pregnancy rate - Choudhary, Manisha; Sharma, Sangita; Swarankar, Mohan Lal; Bhardwaj, Shiv Lal (International Journal of Research in Medical Sciences, 2016)
Background: Premature luteinization (PL) refers to a rise in serum progesterone (P4) levels on the day of HCG administration (1-4). Most studies use an absolute P4 level on the day of HCG administration as an indicator of PL. This study is carried out with the aim to evaluate the incidence of premature luteinizaition (P4 >1.5ng/ml on the day of HCG) and factors influencing it in both agonist and antagonist cycles & its effect on clinical outcome. Methods: 400 Patients treated by IVF/ICSI at Jaipur fertility centre (ART Unit of Mahatma Gandhi University of Medical Sciences and Technology) from January 2014 to June 2015 were included in this retrospective clinical study. 200 patients were taken in agonist group and 200 in antagonist group. Ovulation induction was given with r-FSH/HMG in both protocols. P4 along with E2, LH and number of oocytes on the day of HCG were taken for study. Results: Premature luteinization or PL (P4 > 1.5 ng/ml) was noticed in 16% cases in the agonist group and 6% in the antagonist group (p-0.002). In our study the factors predisposing to PL were agonist protocol (16% Vs. 6%, p-0.002), total dose of gonadotrophins > 2000 IU ( 17.69 % Vs. 2.29, p-0.000), >10 follicles of > 14mm on the day of HCG with E2 Levels > 2500 pg/ml (33.33 % Vs. 0%, p-0.000) in agonist protocol and (17.39% Vs. 2.59%, p-0.000) in antagonist protocol. The clinical pregnancy rate was significantly reduced in cases with PL (32.73% Vs 12.5%, p-0.037) in agonist group. Though the difference was not statistically significant in antagonist group (32.97% Vs 8.33 %, P-0.144),this could be due to large difference in the proportion of sample size. Conclusions: Despite the use of GnRH analogues, risk of premature rise of progesterone is still there. The risk mainly depends on ovarian response. The high responders with high no of > 14mm follicles, high E2 Levels > 2500 pg/ml and high doses of gonadotrophins used are associated with high risk of PL. As premature rise in P4 level has significant Impact on clinical pregnancy rate (CPR), identification of high risk factors & their proper management can reduce the incidence of PL & cycle cancellation rate as well as can improve the clinical outcome.